Embracing the African Continental Free Trade Area: Unpacking Malawi’s Economy Response to Trade Liberalization - Wisdom Richard Mgomezulu; Paul Thangata; Daniel Njiwa (Research in Globalization)
The impact of trade liberalization on Malawi’s economy has been a hotly debated topic. To shed light on the subject, a study was conducted using the PEP-1–1 CGE model and the latest Malawi’s Social Accounting Matrix (SAM) from 2019. The results were eye-opening, revealing the potential effects of the African Continental Free Trade Area (AfCFTA) on various sectors of the economy. The removal of trade tariffs is predicted to have a significant impact on prices, with a decrease of 26.31% in the agricultural sector alone, services (−7.88%), public administration (−9.92%), and manufacturing and industry (−11.23%) imposing hopes of improving food affordability and food security. However, it is expected to have adverse impacts on wage rates in the agricultural sector (−18.78%), manufacturing and construction (−19.01%), services (−2.79%) and public administration (−15.81%). Additionally, while exports are expected to increase, the country’s balance of payments may suffer as imports are likely to outweigh foreign earnings. This could also lead to a decrease in government revenue from taxes. To mitigate these effects, the study suggests implementing export restructuring strategies, particularly in industries like manufacturing and construction, and promoting diversification of local production to boost competitiveness and improve wage rates. With these measures in place, the government will not only offset potential losses but also tap into new sources of taxable income.